Uji Kadar Vitamin C Bawang Dayak dan Bawang Merah Menggunakan Titrasi Iodimetri - Wa Jumi; Evi Mustiqawati; Hasty Hamzah (Politeknik Baubau, 2023)
Vitamin C is an important compound for the human body. The fuction of vitamin C is to form collagen and antioxidants that the body needs. This study aims to determine the levels of vitamin C in dayak onions (Eleutherine Palmifolia (L.) Merr) and red shallots (Allium Ascalocinum L.) using iodimetric titration. To tests the levels of vitamin C using the iodimetric method. The results of vitamin C levels carried out in three consecutive titrations had a concentration value of 46,5 mg/g in dayak onions with an average value of 5,67 mL and a concentration value in shallots of 39,7 mg/g with an average value of 4,8 mL.